LENGUA E HISTORIA EN PLATÓN: ORALIDAD Y ESCRITURA, MYTHOLOGEIN Y MYTHOLOGIA EN EL TIMEO Y EN EL CRITIAS - Amorós Juan, Pedro (Antigüedad y Cristianismo, 1995)
This study explains the search for a new model which would define the relations between history and tradition. In this sense, the Platonical narrations Timeo and Critias enclose deep reflections on the relations between myth, memory and history in the Greek world. Contrary to the general idea held by the historians who consider the narration as a mythos, Platon presents it as a logos. From the fifth century on the Greek illustrated public distinguish between the various types of narrations: verifiable histories of the past, stories of archeological character or credibile logoi, and model mythoi. The Timeo and Critias belong to the second genre, the logographic narration in which the logos is expressed as the traditional language. At the same time, Plato takes into consideration and establishes the differences between mythologein, the oral transmission of the myths, and mythologia, the reflection and investigation of the ancient traditions related to the scripture and with the narrations.